Pelatihan Remaja Tangguh Untuk Menurunkan Homesickness Santri Di Pondok Pesantren - Lisnawati; Rahma, Salsabila Aulia (UIN Sunan Kalijaga, 2025)
Homesickness is a problem that often occurs in students who live in dormitories, including Islamic boarding schools. Resilience is a protective factor in cases of homesickness. The Resilient Youth Training was prepared by researchers based on the concept of resilience to help deal with the problem of homesickness. This research aims to determine the effectiveness of Resilient Youth Training in reducing the level of homesickness in participants. Participants consisted of 18 students aged 12-15 years who were divided into experimental and control groups with 9 participants each. The research design is a two-group pretest and posttest design. Data collection used the Homesickness Questionnaire in the Likert model. Data analysis used the Mann Whitney U-Test, Wilcoxon Signed Rank Test and N-Gain-Score. The results showed significant differences between the experimental and control groups (post-test: p=.012; follow-up: p=0.000). Resilient Youth Training was effective in reducing the level of homesickness in research participants (pretest-posttest: p=0.001; posttest-follow-up: p=0.002), with an N-Gain Score of 52.1% Homesickness merupakan permasalahan yang sering terjadi pada siswa yang tinggal di asrama, termasuk pondok pesantren. Ketangguhan atau resiliensi menjadi salah satu faktor protektif pada kasus homesickness. Pelatihan Remaja Tangguh disusun peneliti berdasar konsep resiliensi untuk membantu menangani permasalahan homesickness. Penelitian ini bertujuan untuk mengetahui efektivitas Pelatihan Remaja Tangguh dalam menurunkan tingkat homesickness pada partisipan. Partisipan terdiri dari 18 santri berusia 12-15 tahun yang terbagi menjadi kelompok eksperimen dan kontrol dengan masing-masing berjumlah 9 partisipan. Desain penelitian adalah two-group pretest and posttest design. Pengumpulan data menggunakan Kuesioner Homesickness model Likert. Analisis data menggunakan Mann Whitney U-Test, Wilcoxon Signed Rank Test dan N-Gain-Score. Hasil menunjukkan perbedaan signifikan antara kelompok eksperimen dan kontrol (post-test: p=0.012; follow-up: p=0.000). Pelatihan Remaja Tangguh efektif dalam mengurangi tingkat homesickness pada partisipan penelitian (pretest-posttest: p=0.001; posttest-follow-up: p=0.002), dengan N-Gain Score sebesar 52.1%.